The Role of Angiogenesis Factors in the Formation of Vascular Changes in Scleroderma by Assessment of the Concentrations of VEGF and sVEGFR2 in Blood Serum and Tear Fluid. (24th January 2020) - Waszczykowska, Arleta; Goś, Roman; Waszczykowska, Elżbieta; Dziankowska-Bartkowiak, Bożena; Podgórski, Michał; Jurowski, Piotr
Abstract : Systemic sclerosis (SSc) is a connective tissue disorder characterized by tissue hypoxia, excessive fibrosis of skin and internal organs, and angiogenesis imbalance. The aim of the study was to evaluate in SSc patients the association between the retinal microcirculation disturbances and the presence of peripheral trophic changes and to determine the role of angiogenesis factors in the formation of vascular changes in scleroderma. Twenty-five SSc patients and 25 age- and sex-matched healthy controls were included to the study. Assay of vascular endothelial growth factor (VEGF) and soluble VEGF receptor-2 (sVEGFR-2) in blood serum and tears was done for all patients and controls using enzyme-linked immunosorbent assay. Retinal blood circulation was investigated with fluorescein angiography (FA) in the SSc patients only. In our research, proportion of mainly hypertensive patients presenting with a large spectrum of retinal microvascular lesions was 72%, while proportion of patients with skin microvascular lesions within distal phalanxes of fingers and toes was 76%. We noticed that patients with pathological changes in the FA examination had finger ulcerations significantly more often than patients without changes in the eye fundus. There were no statistically significant differences in the serum concentration of VEGF and sVEGFR2 between subjects in both analyzed groups. Analysis of lower levels of VEGF (p = < 0.001 ) and sVEGFR-2 (p = < 0.001 ) in blood serum accompanied by simultaneous higher levels of VEGF/sVEGFR-2 ratio in tears of SSc patients, as compared with the control group, indicates the superiority of proangiogenic factors in patients' tears.